Differential associations between Social Anxiety Disorder, family cohesion, and suicidality across racial/ethnic groups: Findings from the National Comorbidity Survey-Adolescent (NCS-A). (May 2017) - Rapp, Amy M.; Lau, Anna; Chavira, Denise A.
Abstract: The proposed research seeks to introduce a novel model relating Social Anxiety Disorder (SAD) and suicide outcomes (i.e., passive suicidal ideation, active suicidal ideation, and suicide attempts) in diverse adolescents. This model posits that family cohesion is one pathway by which suicide risk is increased for socially anxious youth, and predicts that the relationships between these variables may be of different strength in Latino and White subgroups and across gender. Data from a sample of Latino ( n  = 1922) and non-Hispanic White (hereafter referred to as White throughout) ( n  = 5648) male and female adolescents who participated in the National Comorbidity Survey-Adolescent were used for this study. Analyses were conducted using generalized structural equation modeling. Results showed that the mediation model held for White females. Further examination of direct pathways highlighted SAD as a risk factor unique to Latinos for active suicidal ideation and suicide attempt, over and above comorbid depression and other relevant contextual factors. Additionally, family cohesion showed a strong association with suicide outcomes across groups, with some inconsistent findings for White males. Overall, it appears that the mechanism by which SAD increases risk for suicidality is different across groups, indicating further need to identify relevant mediators, especially for racial/ethnic minority youth.